Weight perception and its associated factors among type 2 diabetes mellitus patients attending Diabetes Clinic, Hospital Universiti Sains Malaysia - Mun, Wong Ching (2017)
Background: Weight perception is one of the determining factors of receptivity to weight management intervention especially in diabetes mellitus patients. Weight management is the cornerstone of diabetic management as 5 to 7 percent of weight reduction can reduce oral anti-diabetic agent use and even prevent and delay onset of diabetes. Objective: To determine the weight perception and its associated factors among type 2 diabetes mellitus patients attending diabetic clinic, HUSM Methodology: This was a cross-sectional study conducted among 321 diabetic patients attending diabetic clinic from June 2015 to June 2016. Data on sociodemographic characteristics, diabetic duration and treatment, weight perception, weight management behaviours, measurement of weight and height, physical activities in METS and fibre/vegetables intake were collected using structured questionnaire. Results: A total of 67.9% (n=218) of the participants had underestimated their weight status. Factors associated with under-estimation of weight were being married (AOR=0.09 [95%CI: 0.01-0.76], P=0.23), lower education level (AOR=0.43 [95%CI=0.20-0.92], P=0.028), overweight (AOR=10.15, 95%CI=4.21-24.51, P<0.001) and obese (AOR=5.85, 95%CI=14.73-147.89, P<0.001), and being physically less active (AOR=46.67, 95%CI=2.57-13.30, P<0.001). BMI of the subjects were closely related to estimation, as being overweight is 10 times more likely than normal subjects inunderestimation of their weight status, and obese individuals too, significantly underestimated their weight. Conclusions: We found a mismatch between BMI measured and self-perceived body weight. Health care personnel need to spend more time and effort in patients’ weight perception in order to improve diabetic management and its health relevance.